Interaksi Harmonis dalam Masyarakat Plural: Tinjauan Literatur tentang Kolaborasi Antar Ras, Budaya, Agama, dan Gender - Acep Rahmat Acep Rahmat; Tari Rahmatila; Salsabila Saqina; Rijal Jainal Arifin (Yayasan Al-Afif, 2025)
This research aims to examine harmonious interactions in a pluralistic society with a focus on collaboration between races, cultures, religions and gender through literature review methods. A pluralistic society that is rich in diversity presents both potential and challenges in creating social harmony. This study identifies the basic concepts of harmonious interaction, factors that support cross-group collaboration, challenges faced, and effective practices and policies to promote social harmony. The results of the analysis show that multicultural education, inclusive policies, dialogue between groups, and the role of positive media are key elements in building mutually respectful and supportive interactions. However, challenges such as stereotypes, prejudice, social polarization and sub-optimal policy implementation are still major obstacles. This study provides recommendations for strengthening collaboration through a more inclusive approach, education that supports tolerance, and collaborative initiatives involving various parties. It is hoped that these findings can provide academic and practical contributions in efforts to create a peaceful, inclusive and productive society.